Relationship of Birth Weight to Energy And Thiamin Consumption During the Last Trimester of Pregnancy (Baghdad Science Journal, 2005)
the results pointed out that the average of energy amount obtained by the pregnant women was less than RDA so it amounted to 2014.4 keal/day which caused the birth weight to decrease to 2.8 kg which is less than the normal weight of a new-born child.